Pengajaran Penerjemahan dalam Kelas Penulisan Akademis (Academic Writing) di Universitas Multimedia Nusantara - Niknik M Kuntarto (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2017)
As information and communication technology grows wider and more influential in shaping the training of translators recently, the needs to reformulate translator’s competences are also increasing. By combining some necessary traits and characteristics of good translators coming from the field of linguistics with critical pedagogy fostered in Academic Writing course, the author will argue that translation teaching within the framework of Academic Writing class, yields creativity and more promises on the spirit of keeping humanization alive which is at the same time challenged by the ascent notion of machine translation. The growing dependence on using google translate, for most of the students observed in this case study, highlights the importance to embrace both familiarity with the logic and limitation of MT as well as rootedness within the discourse which empowers human autonomy, thus didactic translation. In this respect, the lecturer plays dual role in becoming role-model for students in translation as well as critical evaluator for their imperfect results of translating text on plagiarism seen from the linguistic phenomenon.